1995
DOI: 10.1021/j100031a011
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of singlet oxygen with peroxy and acylperoxy radicals

Abstract: Quenching of the lowest n,n* triplet states of various diketones and acetone by molecular oxygen was studied by time-resolved ' 0 2 luminescence and nanosecond laser photolysis in solution. The singlet oxygen production efficiency SA in benzene was 0.28 for acetone and 0.28-0.58 for a-diketones. The quenching rate constants of a-diketone triplets by oxygen (kT) are very low, (2-9) x lo8 M-' s-l. A decrease in I 0 2 lifetime was observed upon excitation of a-diketones at laser pulse energies 21 mJ and is explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…For a given N, equations 13b and 14b yield $/IF = K/K' (15) orbital &upancy, and knsequently state symmetries, of 3M1 .12. 49 The lowest energy triplet states of 9-fluorenone and 2-acetonaphthone are r,u* in character, whereas xanthone has nearly degenerate n,u* and r,u* triplet states.50 These differences may influence matrix elements that couple 1.3[3M1. '02(x3Zg-)] and '['Moo -*02(b1Z,+)].…”
Section: Scheme I1mentioning
confidence: 99%
“…For a given N, equations 13b and 14b yield $/IF = K/K' (15) orbital &upancy, and knsequently state symmetries, of 3M1 .12. 49 The lowest energy triplet states of 9-fluorenone and 2-acetonaphthone are r,u* in character, whereas xanthone has nearly degenerate n,u* and r,u* triplet states.50 These differences may influence matrix elements that couple 1.3[3M1. '02(x3Zg-)] and '['Moo -*02(b1Z,+)].…”
Section: Scheme I1mentioning
confidence: 99%
“…The acyl radical (4) that results from this cleavage is trapped by oxygen producing a second epoxidizing agent. 6 Several results support the mechanism of Scheme 1: (1) the reduced singlet oxygen lifetime sensitized by diketones following laser excitation, explained by quenching of singlet oxygen by acylperoxyl radicals, 10 (2) the enhanced photodecomposition of R-diketones under O 2 vs N 2 , 1,6 and (3) the reduced reactivity of benzil in the presence of trans-stilbene, an efficient benzyl triplet quencher. 1,6 The observed epoxidation stoichiometry also supports the proposed mechanism.…”
mentioning
confidence: 69%
“…1,2,6,9,10 Transient absorption spectra were acquired for both species in acetonitrile under oxygen. There was no spectroscopic evidence for a transient with characteristics resembling those for the triplet-oxygen adduct observed in the TL system (see Supporting Information).…”
mentioning
confidence: 99%
“…This metastable level can be reached by absorption of only photons with higher energy and not photons of lower energy, resulting in accumulation of excited molecules in this level. 22 There they facilitate significant absorption of photons with lower energy and, thus, enable holographic recording. Figure 1 depicts the schematic diagram for the above fourlevel system.…”
Section: Principle Of Two-wavelength Photochemicalmentioning
confidence: 99%
“…It has been reported that PQ molecules that reach at T 1 level via π → πà transition have longer lifetime than those via n → πà transition. 22,25,26 This will facilitate more efficient accumulations of PQ molecules. Thus, the wavelength of sensitizing light is chosen to be 325 nm from an He-Cd laser.…”
Section: Wavelength Selection For Sensitizing and Writing Lightmentioning
confidence: 99%